Theoretical Investigation and Design of Novel Cephalosporin Based Inhibitors of a DD-carboxypeptidase Enzyme of Salmonella typhimurium - Ameji John; Adamu Uzairu; Gideon Shallangwa; Sani UBA (Journal of Chemistry Letters)
The rising mortality and morbidity associated with Salmonella typhimurium induced salmonellosis aggravated by the emergence of multi-drug resistant strains of this pathogenic bacterium has made continuous search for novel antibiotics a necessity. In our quest to design newer drug candidates, a series of cephalosporin analogues with significant bioactivities against the aforementioned bacterium were optimized using Density Functional Theorem (DFT) and subjected to Quantitative Structure-Activity Relationship modelling using Multi-linear Regression to harness the dominant descriptors of the antimicrobial properties of the compounds. The validated model (R2 = 0.92, R2Adj = 0.91, Q2LOO = 0.88, R2pred = 0.71, LOF = 0.0001) reveals the predominance of SHBint3, SpMin6_Bhe, and L2u descriptors. Molecular docking simulation of the compounds guided by the model led to the design of two novel ligands, L1 and L2 with binding affinity of -7.7 kcal/mol and -8.3 kcal/mol, respectively against the PBP6 protein target of the bacterium. These values are higher than the -6.7 kcal/mol obtained for cefuroxime (R) antibiotic used as standard for comparison against the same protein target. The newly designed ligands exhibit excellent pharmacokinetic and toxicological profiles as well positive drug-likeness. Using the generated model, Minimum Inhibitory Concentration values of 0.038µg/mL and 0.051µg/mL were predicted for L1 and L2, respectively. The novel ligands displayed a balance of potency, binding affinity, pharmacokinetic and toxicological profiles as well as unique mechanisms of interactions with the PBP6 target of Salmonella typhimurium. We therefore recommend their synthesis, biological evaluation and clinical trial.